IMPLEMENTASI POJOK LITERASI DALAM MENINGKATKAN KETERAMPILAN CRITICAL THINKING SISWA SEKOLAH DASAR - Krista Alifa Setyaningrum; Rido Kurnianto; Aldo Redho Syam (UPT. Perpustakaan Universitas Muhammadiyah Ponorogo, 2023)
The progress of the 21st century has had an effect on the development of education in Indonesia. Competence possessed by students needs to be improved to respond to this. One of the students' abilities that need to be improved is critical thinking. Increasing this competency can be done through the implementation of literacy corners in schools. The application aims to facilitate students in carrying out literacy activities and if it is cultivated it will have various positive impacts on students. This study uses a qualitative method of case study type. Data collection was carried out through observation, interviews, and documentation. The objective of this research is to understand the implementation of literacy corners in enhancing critical thinking for elementary school students. The results of the study indicate that the implementation of literacy corners has successfully improved the critical thinking of Tosanan Elementary School students, characterized by the following aspects: the development of students' logical thinking skills, increased curiosity, improved focus during learning activities, enhanced abilities in formulating and analyzing problems, making decisions, thinking openly, and appreciating the thoughts of others. The implementation of these activities is conducted in three stages: preparation, execution, and evaluation, carried out progressively and sustainably.